Heritage-making: Written Texts in the Transmission of Traditional Knowledge of Natural Dyeing - Karlsone, Anete (The Museum of the Romanian Peasant Anthropology, 2022)
Natural dyeing is an element of intangible cultural heritage which is gaining new relevance today. Heritage-making as a set of purposeful activities has become an object of interest for researchers relatively recently, and this study is reflective of that. The paper aims to focus on natural dyeing as a component of cultural heritage, its documentation process, and how written texts have influenced the living tradition of natural dyeing. One of the sources for the study was ethnographic material, which provides insight into the little researched tradition of natural dyeing. To understand how the tradition was described and explained, Latvian press publications on natural dyeing were evaluated by applying qualitative and quantitative research methods. In order to study the situation today, a survey was conducted in 2016 and 2017 among dyeing workshop participants in different parts of Latvia. The results of the study indicate that the use of written sources plays an important role in practicing natural dyeing. With various activities organized by professional and amateur ethnographers, artists, handicraft teachers, etc., as well as its coverage in the press, natural dyeing has preserved its relevance. Written texts have documented the activities in the field of natural dyeing and encouraged further development of the tradition. Moreover, various sources have been used to preserve and develop dyeing skills, through both direct observation/ oral tradition and written/visual materials. In addition, one’s personal experience as a significant part of the construction of identity was relevant in the past and still is today
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Ethnology::Cultural anthropology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Heritage studies; heritage-making; natural dyeing; traditional craftsman ship; Latvia